2023
DOI: 10.1108/ijcma-09-2022-0157
|View full text |Cite
|
Sign up to set email alerts
|

Toward an event-oriented conceptualization of conflict: reflections on three decades of conflict research

Abstract: Purpose How to depict conflict characteristics? Previous literature has overwhelmingly used intensity and frequency of conflict, resulting in an incomplete understanding of conflict itself and its impacts. To fill this knowledge gap, this paper aims to develop a comprehensive theoretical framework for conflict attributes. Design/methodology/approach Through a systematic and integrative literature review, this study has achieved the objectives by synthesizing the current state of knowledge on conflict and bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Highly cited reviews identified in this study, along with other relevant ones, can be consulted to gain a comprehensive understanding of knowledge accumulation (Loughry and Amason, 2014; O’Neill and McLarnon, 2018; Pai and Bendersky, 2020; Bradley et al , 2015; Jehn et al , 2015; Poitras, 2012; Schmidt et al , 2014; Hülsheger et al , 2009). Current scholarly efforts focus not only on refining conflict categorization and but also on conceptualizing conflict with nuanced attributes (Zhang et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly cited reviews identified in this study, along with other relevant ones, can be consulted to gain a comprehensive understanding of knowledge accumulation (Loughry and Amason, 2014; O’Neill and McLarnon, 2018; Pai and Bendersky, 2020; Bradley et al , 2015; Jehn et al , 2015; Poitras, 2012; Schmidt et al , 2014; Hülsheger et al , 2009). Current scholarly efforts focus not only on refining conflict categorization and but also on conceptualizing conflict with nuanced attributes (Zhang et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging theoretical streams, including conflict asymmetry, conflict expression, system dynamics framework, conflict history and memory and conflict contagion and concentration, warrant further empirical evidence and critical reviews (Zhang et al , 2023). For example, Shah et al (2021) suggest that exploring conflict evolution across different time and levels of analysis can yield significant insights into conflict patterns and their impact on teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation